Bukhta Kulku po opisi Gidrograficheskoĭ Ėkspedt︠s︡īi Vostochnago okean 1912 g. . Astronomich. p. i skch. k. opredi︠e︡leny General-maĭor Zhdanko vʺ 1912 godu / Sʺemka Kapitana dalʹni︠a︡go pi︠a︡vanīa N. Dobrzhanskago - Russia. Гидрографическій департмент; Russia. Gidrograficheskīĭ departament (Vladivostokʺ : Morskoe ministerstvo, Gidrograficheskīĭ departament; Владивостокъ : Морское министерство, Гидрографическій департмент, 1912)
Relief shown by contours, hachures and spot heights. Depths shown by soundings and isolines.; "Masshtabʺ 1/16800 ili 200 s. vʺ 1 d." [Scale 1/16800 or 200 sazhens in 1 inch].; "Okhotskoe More No. 215" [Sea of Okhotsk No. 215] -- across top margin Grayscale; 1:16,800